A polyvinylphosphoric acid type phosphomolybdicvanadium heteropolyacid catalyst, its preparation method and its application in deep oxidation desulfurization with low oxygen-sulfur ratio

By using polyvinyl phosphoric acid type phosphomolybdenum vanadium heteropoly acid catalyst, the problems of low oxidant utilization rate and slow reaction speed in the existing oxidative desulfurization technology are solved, deep oxidative desulfurization with low oxygen to sulfur ratio is achieved, and the desulfurization efficiency is improved and Reduced energy consumption.

CN118620113BActive Publication Date: 2025-01-24HAINAN NORMAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410655040.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-24
Publication Date
2025-01-24
Estimated Expiration
2044-05-24

AI Technical Summary

Technical Problem

In the existing oxidative and desulfurization technology, the solubility of hydrogen peroxide is limited, resulting in slow reaction speed, unsatisfactory desulfurization effect, and low utilization rate of oxidizer.

Method used

Polyvinyl phosphoric acid type phosphomolybdenum vanadium heteropoly acid catalyst is used. This catalyst increases the specific surface area and active sites through polymerization and microwave graphitization, improves desulfurization efficiency, and significantly reduces the amount of hydrogen oxide.

Benefits of technology

It achieves deep oxidation desulfurization with low oxygen to sulfur ratio, significantly improves desulfurization efficiency, reduces energy consumption, and the catalyst is easy to recycle and reuse, which is environmentally friendly, safe, and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118620113B_ABST
    Figure CN118620113B_ABST
Patent Text Reader

Abstract

The invention discloses a polyvinyl phosphoric acid type phosphorus molybdenum vanadium heteropoly acid catalyst, a preparation method thereof and a deep oxidation desulfurization application with a low oxygen-sulfur ratio. The polyvinyl phosphoric acid type phosphorus molybdenum vanadium heteropoly acid catalyst has a general structural formula of P-VIA-Mo n V m , wherein P is a polymer, VIA is vinyl phosphoric acid, and n and m are real numbers of 1 to 14. The present invention polymerizes vinyl phosphoric acid to prepare phosphomolybdic vanadic acid, and then performs microwave drying, thereby increasing the specific surface area of ​​the heteropoly acid, increasing the active sites involved in the catalytic activity, and achieving the optimal effect under a low oxygen-sulfur ratio, significantly improving the catalytic oxidation desulfurization efficiency, and the desulfurization conditions are mild, easy to operate, low in energy consumption, high efficiency, economy, and environmental protection; easy to recycle, recyclable, and low in cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a polyvinylphosphoric acid type phosphomolybdicvanadium heteropolyacid catalyst, a preparation method thereof and an ultra-deep oxidation desulfurization application of the catalyst with an ultra-low oxygen-sulfur ratio, and belongs to the cross-technical field of environmental protection technology and oil product chemical deep processing industry. Background Art

[0002] In recent years, with the continuous development of industrial society, chemical fuels such as gasoline, diesel, and kerosene have been widely used in industrial production. However, during the combustion process, a large amount of oxygenated sulfides (SOx) will be emitted into the air, causing atmospheric pollution. Continuously reducing the sulfur content in fuel oil and achieving "zero" sulfur content in fuel oil is an inevitable trend in the development of the fuel industry in the future. The production of ultra-low sulfur fuel oil is an important task in the oil refining industry, and the development of deep desulfurization technology has become the goal of researchers around the world.

[0003] At present, oxidative desulfurization is regarded as one of the most promising desulfurization technologies, and has attracted much attention due to its mild reaction conditions, simple operation and low energy consumption. Its core principle is to convert sulfur compounds in fuel, such as thiophene sulfur, into corresponding sulfoxides or sulfones through oxidation reactions. Since the oxidation products have higher polarity, they can be effectively extracted using polar solvents, thereby achieving the goal of desulfurization.

[0004] The choice of oxidant in oxidative desulfurization technology affects the desulfurization effect. Common oxidants include ozone, oxygen, organic peroxyacids, hydrogen peroxide, etc., but hydrogen peroxide is usually selected as the oxidant because of its low corrosiveness and environmental protection. However, the solubility of hydrogen peroxide in the oil phase is limited, which affects the full contact between gasoline and the oxidant, thereby reducing the reaction rate and resulting in unsatisfactory desulfurization effect. This can be solved by using a phase transfer catalyst. The phase transfer catalyst can increase the reaction rate of two reactants in an immiscible solvent (such as a liquid-liquid two-phase system, a solid-liquid two-phase system). As a bridge between the two phases, it can transfer the reactants from one phase to another during the reaction process, so that the reactants are fully in contact with the substrate, thereby ensuring the desulfurization efficiency.

[0005] As an emerging type of catalytic material, heteropolyacids have a relatively small surface area and are prone to agglomeration during the reaction, so their catalytic performance is limited to a certain extent. However, these problems can be effectively overcome by loading heteropolyacids onto a carrier, and this method is favored by experts in the field of catalysis. Catalysts loaded on different carriers are suitable for different types of reactions. There are some challenges for heteropolyacid-loaded catalysts required for deep desulfurization. For example, some catalysts are easily soluble in the ionic liquid phase and are difficult to recover and reuse, or may have certain toxicity, and the cost is relatively high, or the desulfurization effect is poor. At the same time, the utilization rate of the oxidant is low, and usually an O / S (molar ratio) ≥ 7 is required to achieve a relatively good desulfurization effect. Summary of the invention

[0006] The present invention provides a polyvinylphosphoric acid type phosphomolybdicvanadium heteropolyacid catalyst, a preparation method thereof and its application in deep oxidation desulfurization with a low oxygen-sulfur ratio. The catalyst of the present invention has mild desulfurization conditions and is simple to operate. It can effectively remove sulfides from oil products and significantly reduces the amount of hydrogen peroxide used, thereby achieving deep oxidation desulfurization with a low oxygen-sulfur ratio.

[0007] In order to solve the above technical problems, the technical solutions adopted by the present invention are as follows:

[0008] A polyvinylphosphoric acid type phosphomolybdicvanadium heteropolyacid catalyst, the general structural formula of which is P-VIA-Mo n V m , wherein P is a polymer, VIA is vinyl phosphonic acid, and n and m are real numbers ranging from 1 to 14.

[0009] The above n is preferably a real number of 7-14, and m is preferably a real number of 7-14.

[0010] The polyvinylphosphoric acid type phosphomolybdicvanadium heteropolyacid catalyst has a large specific surface area and many active sites.

[0011] The preparation method of the polyvinylphosphoric acid type phosphomolybdicvanadic heteropolyacid catalyst comprises the following steps:

[0012] (1) dissolving 1-vinyl phosphonic acid (1-VIA) and azobisisobutyronitrile (AIBN) in acetonitrile, polymerizing at 80-90° C. for 18-24 h under N2 protection to obtain a polymer;

[0013] (2) The polymer obtained in step (1), molybdenum trioxide, vanadium pentoxide and deionized water are mixed and reacted at 90-100° C. and 500-650 rpm for 18-24 hours to obtain a catalyst solution, which is then microwave dried to obtain a polyvinylphosphoric acid type phosphomolybdicvanadium heteropolyacid catalyst. The microwave drying is preferably performed at 800 W for 5 minutes.

[0014] In the above step (2), microwave catalysis is used, which has a short cycle, high efficiency, good safety, high efficiency of the obtained catalyst, and no special atmosphere is required. If the existing graphitization furnace is used, the temperature is too high and the catalyst will become oxides and the catalytic effect cannot be achieved. If the temperature is too low, the catalytic effect cannot be achieved.

[0015] The above method uses microwave graphitization to graphitize polyethylene-type phosphomolybdic vanadic acid, thereby increasing the specific surface area of ​​the heteropoly acid, thereby increasing the active sites involved in the catalytic activity, improving the desulfurization efficiency, and the conditions are mild.

[0016] In order to further improve the catalytic effect, the mass ratio of the above-mentioned vinyl phosphoric acid and azobisisobutyronitrile is (30-35):1; the molar ratio of MoO3 to V2O5 is 7:1-14:1; and the molar ratio of MoO3 to 1-vinyl phosphoric acid is 7:1-14:1.

[0017] In order to improve the reaction efficiency, in step (2), the mass amount of deionized water used is 9 to 23 times the sum of the mass of MoO3 and V2O5.

[0018] In order to better ensure the catalytic effect, in step (2), the microwave drying time is 3-5 minutes and the power is 800W.

[0019] The polyvinylphosphoric acid type phosphomolybdicvanadium heteropolyacid catalyst prepared by the above method can be used for catalytic oxidation desulfurization.

[0020] The present application can utilize the principle of combining catalytic oxidation with extraction separation to remove sulfur-containing compounds in oil products, and the extraction separation directly refers to the existing mature technology.

[0021] As one of the specific implementation schemes, the steps of catalytic oxidation desulfurization are as follows: after pre-mixing the oil to be desulfurized and the ionic liquid, add polyvinyl phosphate type phosphomolybdenum-vanadium heteropolyacid catalyst and H2O2 water, and achieve deep desulfurization of the oil to be tested under normal temperature and pressure conditions. For the same catalyst, the desulfurization effect of selecting different ionic liquids is different, and the difference is even very large. The preferred ionic liquid in this application is 1-octyl-3-methylimidazole tetrafluoroborate.

[0022] In order to ensure the desulfurization effect, the mass of the polyvinyl phosphoric acid type phosphomolybdic vanadium heteropoly acid catalyst is 0.1%-2% of the mass of the oil to be desulfurized. The mass concentration of the H2O2 aqueous solution is 25-35%, preferably 30%.

[0023] In order to reduce energy consumption and ensure reaction efficiency, the desulfurization reaction temperature is 20-30°C; the reaction time is 10-20min; the amount of H2O2 is calculated as follows: the molar number of H2O2 is determined by the molar number of sulfur (S) in the oil to be treated, and the O / S molar ratio is ≤3. The present application significantly reduces the amount of hydrogen peroxide and improves the utilization rate of the oxidant. In O / S, O refers to O in H2O2 and does not include O in water. Excessive use of H2O2 not only wastes resources, but the inventors have found that excessive use of H2O2 will affect the desulfurization effect.

[0024] The present invention can complete the desulfurization reaction at room temperature, which not only significantly saves energy consumption, but also saves the cost of purchasing heating equipment. The desulfurization time is also shortened from the existing 30 minutes to less than 20 minutes, which significantly improves the desulfurization efficiency, and also significantly reduces the amount of hydrogen peroxide, achieving deep oxidation desulfurization with a low oxygen-sulfur ratio.

[0025] The present invention can realize the recovery and reuse of the catalyst by sedimentation, filtration and drying, which is simple and convenient, easy for enterprises to promote, environmentally friendly and safe, with good desulfurization effect and low cost.

[0026] The technologies not mentioned in the present invention are all referred to the prior art.

[0027] The polyvinyl phosphoric acid type phosphomolybdic-vanadium heteropolyacid catalyst of the present invention polymerizes 1-vinyl phosphoric acid first, then reacts with molybdenum trioxide and vanadium pentoxide, and finally microwaves to dry, thereby increasing the specific surface area of ​​the heteropolyacid and the active sites involved in the catalytic activity, significantly reducing the amount of hydrogen oxide used while ensuring a highly efficient and mild desulfurization effect, improving the utilization rate of the oxidant, being easy to operate, having low energy consumption, being easy to recycle, and being recyclable, thereby improving the utilization rate of resources. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 A scanning electron microscope image of the vinyl phosphoric acid type phosphomolybdic vanadium heteropoly acid P-VIA-Mo7V catalyst prepared in Example 1;

[0029] Figure 2 The vinyl phosphate type phosphomolybdic vanadium heteropoly acid P-VIA-Mo prepared in Example 2 14 Scanning electron micrograph of V catalyst;

[0030] Figure 3 The vinyl phosphate type phosphomolybdic vanadium heteropoly acid P-VIA-Mo prepared in Example 3 14 Scanning electron micrograph of the V7 catalyst;

[0031] Figure 4 The vinyl phosphate type phosphomolybdic vanadium heteropoly acids P-VIA-Mo7V, P-VIA-Mo prepared in Examples 1, 2, and 3 are 14V, and P-VIA-Mo 14 Fourier transform infrared spectrum of V7 catalyst;

[0032] Figure 5 This is a curve diagram of desulfurization efficiency variation over time in Example 4;

[0033] Figure 6 The polyvinyl phosphoric acid type phosphomolybdic vanadium heteropoly acid P-VIA-Mo in Example 4 14 Results graph of V7 cycle use;

[0034] Figure 7 The polyvinyl phosphoric acid type phosphomolybdic vanadium heteropoly acid P-VIA-Mo in Example 6 14 Results graph of V7 cycle use;

[0035] Figure 8 It is a curve diagram of desulfurization efficiency changing with time in Comparative Example 1;

[0036] Fig. 9 It is a curve diagram of desulfurization efficiency changing with time in Comparative Example 2;

[0037] Fig.10 The curve of desulfurization efficiency changing with time in Comparative Example 3; DETAILED DESCRIPTION

[0038] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0039] The room temperature in each case was 20 to 30° C. When the conversion rate reached 99.9999% or more, it was regarded as 100% conversion.

[0040] Example 1

[0041] Preparation of polyvinylphosphoric acid type phosphomolybdicvanadic heteropoly acid P-VIA-Mo7V:

[0042] By bulk polymerization, 0.54 g of 1-vinyl phosphoric acid (1-VIA) and 0.0162 g of azobisisobutyronitrile (AIBN) were placed in a reaction bottle, and then 5 ml of acetonitrile was added to dissolve it and sealed. Under N2 protection, the polymerization was carried out at 85°C with stirring (650 rpm) for 24 h. After the reaction, the obtained polymer was transferred and mixed with 5.04 g of MoO3 and 0.46 g of V2O5, added to 125 mL of deionized water, condensed and refluxed to 95°C, stirred (650 rpm) and reacted for 24 h to obtain a P-VIA-Mo7V catalyst solution, and then microwave dried (800 W, 5 min, the material was divided into 50 ml crucibles for drying, each crucible was about 5 ml to avoid overflow during microwave drying) to obtain a polyvinyl phosphoric acid type molybdenum-vanadium heteropoly acid P-VIA-Mo7V catalyst. The scanning electron microscope image (SEM) is shown as follows Figure 1 As shown by Figure 1 It can be seen that the obtained catalyst is a material with uniform size distribution; the Fourier infrared spectrum is as follows Figure 4 As shown by Figure 4 It can be seen that 1080cm -1 , 968cm -1 and 829cm -1 The left and right are the characteristic peaks of heteropolyacids with Keggin structure, indicating that polyvinylphosphoric acid type phosphomolybdenumvanadium heteropolyacid P-VIA-Mo7V was successfully prepared.

[0043] Example 2

[0044] Polyvinylphosphoric acid type phosphomolybdicvanadic heteropoly acid P-VIA-Mo 14 Preparation of V:

[0045] Using bulk polymerization method, 0.54g 1-vinyl phosphonic acid (1-VIA) and 0.0162g azobisisobutyronitrile (AIBN) were placed in a reaction bottle, and then 5ml acetonitrile was added to dissolve it and sealed. Under N2 protection, the polymerization was stirred at 85℃ (650rmp) for 24h. After the reaction, the obtained polymer was transferred and mixed with 10.08g MoO3 and 0.46g V2O5, added to 125mL deionized water, condensed and refluxed, heated to 95℃, stirred (650rmp) and reacted for 24h to obtain P-VIA-Mo 14 V catalyst solution. 14 The V catalyst solution was microwave dried (800W, 5min, the material was divided into 50ml crucibles for drying, about 5ml in each crucible to avoid overflow during microwave drying), and then microwave dried to obtain P-VIA-Mo 14 V catalyst, scanning electron microscope (SEM) Figure 2 As shown by Figure 2It can be seen that the obtained catalyst is a lamellar material; the Fourier infrared spectrum is as follows Figure 4 As shown by Figure 4 It can be seen that 1080cm -1 , 968cm -1 and 829cm -1 The left and right are the characteristic peaks of Keggin structure heteropoly acid, indicating the successful preparation of polyvinyl phospho-molybdovanadophosphoric acid heteropoly acid P-VIA-Mo 14 V.

[0046] Example 3

[0047] Polyvinylphosphoric acid type phosphomolybdicvanadic heteropoly acid P-VIA-Mo 14 Preparation of V7:

[0048] Using bulk polymerization, 0.54g 1-vinyl phosphonic acid (1-VIA) and 0.0162g azobisisobutyronitrile (AIBN) were placed in a reaction bottle, and then 5ml acetonitrile was added to dissolve it and sealed. Under N2 protection, the polymerization was stirred at 85℃ (650rmp) for 24h. After the reaction, the obtained polymer was transferred and mixed with 10.08g MoO3 and 3.22g V2O5, added to 125mL deionized water, condensed and refluxed, heated to 95℃, stirred (650rmp) and reacted for 24h to obtain P-VIA-Mo 14 V7 catalyst solution. 14 The V7 catalyst solution was microwave dried (800W, 5min, the material was divided into 50ml crucibles for drying, about 5ml in each crucible to avoid overflow during microwave drying), and then microwave dried to obtain P-VIA-Mo 14 V7 catalyst, scanning electron microscope (SEM) Figure 3 As shown by Figure 3 It can be seen that the obtained catalyst is a porous material with loose nanostructure; the Fourier infrared spectrum is shown in Figure 4 As shown by Figure 4 It can be seen that 1080cm -1 , 968cm -1 and 829cm -1 The left and right are the characteristic peaks of Keggin structure heteropoly acid, indicating the successful preparation of polyvinyl phospho-molybdovanadophosphoric acid heteropoly acid P-VIA-Mo 14 V7.

[0049] Example 4

[0050] Taking dibenzothiophene (DBT), which is difficult to remove in hydrodesulfurization, as a representative, DBT was dissolved in 100 mL of 92# gasoline to prepare a simulation system with a sulfur content of 500 ppm, 1 mL of ionic liquid 1-octyl-3-methylimidazolium tetrafluoroborate was added, and the mixture was stirred and mixed. The amount of H2O2 added was calculated according to O / S (molar ratio) = 3, and the polyvinyl phosphoric acid type molybdenum vanadium heteropoly acid P-VIA-Mo prepared in Example 3 was calculated according to 1% of the mass of 92# gasoline. 14 The amount of V7 added was 30% H2O2 and polyvinyl phosphoric acid type phosphomolybdic vanadium heteropoly acid P-VIA-Mo 14 V7 is added to the above simulation system, such as Figure 5 As shown in FIG. 1 , after 20 minutes of reaction at room temperature, the conversion rate (desulfurization rate) of DBT in 92# gasoline reached nearly 100%. The catalyst prepared in Example 1-2 was tested in the same manner, and the results were as follows: Figure 5 As shown by Figure 5 It can be seen that polyvinyl phosphoric acid type phosphomolybdic vanadium heteropoly acid P-VIA-Mo7V (prepared in Example 1), polyvinyl phosphoric acid type phosphomolybdic vanadium heteropoly acid P-VIA-Mo 14 V (prepared in Example 2) and polyvinylphosphoric acid type phosphomolybdicvanadic heteropoly acid P-VIA-Mo 14 The removal effect of V7 (prepared in Example 3) on DBT reached 100%.

[0051] The polyvinyl phosphate type phosphomolybdic vanadium heteropoly acid P-VIA-Mo in each example is recovered by sedimentation, filtration and drying. 14 V7, P-VIA-Mo 14 V and P-VIA-Mo7V, the recovery rate is above 99.9%. Figure 6 As shown, the catalytic efficiency was hardly reduced (the reduction was only about 0.2%) when the recovered catalyst was recycled 25 times.

[0052] Example 5

[0053] Taking dibenzothiophene (DBT), which is difficult to remove in hydrodesulfurization, as a representative, DBT was dissolved in 100 mL of 95# gasoline to prepare a simulation system with a sulfur content of 500 ppm, 1 mL of ionic liquid 1-octyl-3-methylimidazolium tetrafluoroborate was added, and the mixture was stirred. The amount of H2O2 added was calculated according to O / S (molar ratio) = 3, and the amount was calculated according to 1% of the mass of 95# gasoline. Example 3 Polyvinylphosphoric acid type phosphomolybdic vanadium heteropoly acid P-VIA-Mo 14 V7 catalyst addition amount, H2O2 (mass concentration 30%) polyvinyl phosphoric acid type phosphomolybdic vanadium heteropoly acid P-VIA-Mo 14 After V7 was added into the above simulation system and reacted at room temperature for 20 minutes, the conversion rate of DBT in 95# gasoline reached 100%.

[0054] Example 6

[0055] Taking 4,6-dimethyldibenzothiophene (4,6-DMDBT), which is difficult to remove in hydrodesulfurization, as a representative substance, 4,6-DMDBT was dissolved in 100 mL of 95# gasoline to prepare a simulation system with a sulfur content of 500 ppm, 1 mL of ionic liquid 1-octyl-3-methylimidazolium tetrafluoroborate was added, and the mixture was stirred and mixed. The amount of H2O2 added was calculated according to O / S (molar ratio) = 3, and the amount of H2O2 added was calculated according to 1% of the mass of 95# gasoline. Example 3 Polyvinyl phosphoric acid type phosphomolybdic vanadium heteropoly acid P-VIA-Mo 14 V7 addition amount, H2O2 (mass concentration 30%) and polyvinyl phosphoric acid type phosphomolybdic vanadium heteropoly acid P-VIA-Mo 14 After V7 was added into the above simulation system and reacted at room temperature for 20 minutes, the conversion rate of 4,6-DMDBT in 95# gasoline reached more than 99.8%.

[0056] The polyvinyl phosphate type phosphomolybdic vanadium heteropoly acid P-VIA-Mo in the above materials is recovered by sedimentation, filtration and drying. 14 V7, the recovery rate is above 99.9%, such as Figure 7 As shown, after 20 cycles, the catalytic efficiency decreased by 0.4%.

[0057] Comparative Example 1

[0058] Taking dibenzothiophene (DBT) which is difficult to remove in hydrodesulfurization as a representative, DBT was dissolved in 100 mL of 92# gasoline to prepare a simulation system with a sulfur content of 500 ppm, 1 mL of ionic liquid 1-butyl-3-methylimidazolium tetrafluoroborate was added, and the mixture was stirred. The amount of H2O2 added was calculated according to O / S (molar ratio) = 3, and H2O2 (mass concentration 30%) was added to the above simulation system. Figure 8 As shown, after reacting at 30°C for about 60 minutes, the conversion rate of DBT in 92# gasoline is only about 37%.

[0059] Comparative Example 2

[0060] The difference from Example 4 is that the ionic liquid is replaced by 1-octyl-3-methylimidazole hexafluorophosphate, and the rest is the same as Example 4. The catalyst used is polyvinyl phosphate type phosphomolybdic vanadium heteropoly acid P-VIA-Mo 14 V7, such as Fig. 9 As shown, after reacting at 30°C for about 60 minutes, the conversion rate (desulfurization rate) of DBT in 92# gasoline is only 70%.

[0061] Comparative Example 3

[0062] The difference from Example 4 is that the amount of H2O2 added is calculated according to the O / S (molar ratio) = 7, and the rest is the same as Example 4. The catalyst used is polyvinyl phosphoric acid type phosphomolybdic vanadium heteropoly acid P-VIA-Mo 14 V7, such as Fig. 9 As shown, after reacting at 30°C for about 20 minutes, the conversion rate (desulfurization rate) of DBT in 92# gasoline is only about 97%.

Claims

1. An application of a polyvinylphosphoric acid type phosphomolybdicvanadic heteropolyacid catalyst, characterized in that: Used for catalytic oxidation desulfurization with low oxygen-sulfur ratio, the method for catalytic oxidation desulfurization with low oxygen-sulfur ratio is: after premixing the oil to be desulfurized and the ionic liquid, adding polyvinyl phosphoric acid type phosphomolybdic vanadium heteropoly acid catalyst and H2O2 water, realizing deep desulfurization of the oil to be tested under normal temperature and pressure conditions, wherein the ionic liquid is 1-octyl-3-methylimidazole tetrafluoroborate; the amount of H2O2 water is calculated as follows: the molar number of H2O2 is determined by the molar number of sulfur in the oil to be treated, and the O / S molar ratio is ≤3; The general structural formula of the polyvinylphosphoric acid type phosphorus molybdenum vanadium heteropoly acid catalyst is P-VIA-Mo n V m , wherein P is a polymer, VIA is vinyl phosphonic acid, and n and m are real numbers ranging from 1 to 14; The preparation method of polyvinylphosphoric acid type phosphomolybdicvanadium heteropolyacid catalyst comprises the following steps: (1) Dissolve 1-vinyl phosphonic acid and azobisisobutyronitrile in acetonitrile, and polymerize at 80-90°C for 18-24h under N2 protection to obtain a polymer; (2) The polymer obtained in step (1), molybdenum trioxide, vanadium pentoxide and deionized water are mixed and reacted at 90-100° C. and 500-650 rpm for 18-24 hours to obtain a catalyst solution, which is then dried by microwave to obtain a polyvinylphosphoric acid type phosphomolybdicvanadium heteropolyacid catalyst.

2. The use of the polyvinylphosphoric acid type phosphomolybdicvanadic heteropolyacid catalyst as claimed in claim 1, characterized in that: In step (1), the mass ratio of vinyl phosphonic acid to azobisisobutyronitrile is (30-35):

1.

3. The use of a polyvinylphosphoric acid type phosphorus molybdenum vanadium heteropolyacid catalyst as claimed in claim 1 or 2, characterized in that: The molar ratio of molybdenum trioxide in step (2) to 1-vinyl phosphoric acid in step (1) is 7:1-14:1; and the molar ratio of molybdenum trioxide to vanadium pentoxide in step (2) is (7-14):(1-7).

4. The use of a polyvinylphosphoric acid type phosphorus molybdenum vanadium heteropolyacid catalyst as claimed in claim 1 or 2, characterized in that: In step (2), the mass amount of deionized water used is 9 to 23 times the mass sum of MoO3 and V2O5.

5. Use of the polyvinylphosphoric acid type phosphorus molybdenum vanadium heteropolyacid catalyst as claimed in claim 1 or 2, characterized in that: In step (2), the microwave drying time is 3-5 min and the power is 800 W.

6. The use of the microwave graphitization supported heteropoly acid salt catalyst as claimed in claim 1 or 2, characterized in that: The volume ratio of the ionic liquid to the volume of the oil to be desulfurized is 1:(95~105).

7. Use of the polyvinylphosphoric acid type phosphomolybdicvanadium heteropolyacid catalyst as claimed in claim 1 or 2, characterized in that: The desulfurization reaction temperature is 15-30℃; the reaction time is 10-20min; after the desulfurization reaction temperature is over, the catalyst is precipitated, filtered, dried, and the polyvinyl phosphoric acid type phosphomolybdic vanadium heteropoly acid catalyst is recovered and recycled, with a recovery rate of >99.9%. The catalytic efficiency reduction of 92# gasoline desulfurization after 25 cycles is ≤0.2%, and the catalytic efficiency reduction of 95# gasoline desulfurization after 25 cycles is ≤0.5%.

Citation Information

Patent Citations

  • Titanium-based multi-metal oxide catalyst for removing diesel engine NOx by NH3-SCR in wide temperature window

    CN101898136A

  • Method for preparing 2-ethyl hexanoic acid by catalytically oxidizing 2-ethylhexanal by molybdovanadophosphoric acid

    CN102701944A